Distress Mediates the Association Between Personality Predispositions and Suicidality: A Preliminary Study in a Portuguese Community Sample - Campos, Rui C. (2013)
The present study examined whether distress mediates the relationship between suicidality and the personality predispositions of Self-Criticism, Dependency / Neediness, and Efficacy. A community sample of Portuguese young adults (N¼105) completed, in a counterbalanced order, a sociodemographic questionnaire, the Depressive Experiences Questionnaire (DEQ), the Brief Symptom Inventory (BSI), and reports of any suicide attempts and=or ideation. Structural equation modelling indicated that Self-Criticism is significantly associated with suicidality, but Dependency and Efficacy are not. High levels of Self-Criticism and of Dependency and low levels of Efficacy are associated with distress. Distress mediates the association between Self-Criticism and suicidality; whereas Dependency and Efficacy are indirectly associated with suicidality through their associations with distress. Self-Critical and Dependent individuals are at greater risk for suicide because of their vulnerability to distressful events; whereas certain levels of Efficacy may decrease vulnerability to distress and suicide risk